The Influence of Entrepreneurship and Digital Technology on the Development of MSME Entrepreneurs through E-Commerce Methods in Bandung City: Yudi Surjadi yudisurjadi@gmail.com - Yudi Surjadi (Universal Journal, 2024)
This study aims to explore the impact of digital technology and E-Commerce entrepreneurship methods on the development of MSMEs in Bandung City. The research adopts a quantitative, scientific approach to examine various aspects and phenomena, focusing on causality and their interrelationships. The objective of this quantitative research is to develop and apply mathematical statistical models, theories, and/or hypotheses related to the observed phenomena. The study targets MSME actors in the fashion and culinary sectors in Bandung City, utilizing primary data for analysis. Data collection was conducted through questionnaires, with a saturated sampling method applied for sample selection. The research data were analyzed using multiple linear regression, including validity tests, reliability tests, classical assumption tests, and hypothesis tests. The findings of this study reveal two key conclusions: (1) Entrepreneurial Orientation and Digital Technology significantly and positively influence the development of MSME entrepreneurs, and (2) The application of E-Commerce methods in entrepreneurship significantly and positively impacts the development of MSMEs.